2018
DOI: 10.3390/ijerph15081708
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Use of Copenhagen Burnout Inventory in Italian Sample of University Professors

Abstract: Academics often have to face with burnout syndrome at work. This cross-sectional study evaluates the reliability of the Italian version of the Copenhagen Burnout Inventory (CBI) in a sample of Academics of Sapienza University of Faculty of Medicine and Pharmacy, through an online questionnaire composed of the CBI, SF12 Health Survey, and Positivity Scale. Univariate, bivariate, multivariate analyses, and Cronbach α coefficients of CBI were performed. Ninety-five participants completed the questionnaire (respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 38 publications
0
32
0
2
Order By: Relevance
“…Milfont et al (2008) carried out their study in order to evaluate BS in New Zealand secondary school teachers and identified mean scores of 43.0, 41.5, and 40.4 for PB, WB, and CB, respectively. Sestili et al (2018) identified mean scores of PB = 41.4 and WB = 34.3 (the mean score of CB was not mentioned by the authors). Additionally, they observed that personal and work-related burnout levels were higher in women, younger, and part-time professors, corroborating other results of this study.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Milfont et al (2008) carried out their study in order to evaluate BS in New Zealand secondary school teachers and identified mean scores of 43.0, 41.5, and 40.4 for PB, WB, and CB, respectively. Sestili et al (2018) identified mean scores of PB = 41.4 and WB = 34.3 (the mean score of CB was not mentioned by the authors). Additionally, they observed that personal and work-related burnout levels were higher in women, younger, and part-time professors, corroborating other results of this study.…”
Section: Discussionmentioning
confidence: 92%
“…Like the MBI, the CBI has been used to analyze the BS in human services workers (Kristensen et al, 2005;Molinero, Basart, & Moncada, 2013;Berat et al, 2016), health professionals (Chou, Li, & Hu, 2014;Chin et al, 2018), university students (Marôco & Campos, 2012;Campos et al, 2013), and university professors and academic staff (Kinman & Wray, 2014;Milfont et al, 2008;Avanzi et al, 2013;Fiorilli et al, 2015;Sestili et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Τα τελευταία χρόνια έχουν αναπτυχθεί και άλλα εργαλεία, όπως το Copenhagen Burnout Inventory (CBI), τo οποίο δηµιουργήθηκε από ερευνητές του Εθνικού Ινστιτούτου Υγείας της Εργασίας της ∆ανίας (Kristensen et al 2005). Η κλίµακα CBI έχει µεταφραστεί και έχει χρησιµοποιηθεί σε πολλές µελέτες διεθνώς µε περισσότερες από 1300 ετεροαναφορές (Lin & Lin 2013, Sestili et al 2018, Walters et al 2018.…”
Section: ερευνητικη εργασιαunclassified
“…Τα τελευταία χρόνια έχουν αναπτυχθεί και άλλα εργαλεία, όπως το Copenhagen Burnout Inventory (CBI), τo οποίο δημιουργήθηκε από ερευνητές του Εθνικού Ινστιτούτου Υγείας της Εργασίας της Δανίας (Kristensen et al 2005). Η κλίμακα CBI έχει μεταφραστεί και έχει χρησιμοποιηθεί σε πολλές μελέτες διεθνώς με περισσότερες από 1300 ετεροαναφορές (Lin & Lin 2013, Sestili et al 2018, Walters et al 2018.…”
Section: συμβολή των συγγραφέωνunclassified